Methionine-based carbon monoxide releasing polymer for the prevention of biofilm formation - Maiti, Binoy; Ng, Gervase; Abramov, Alex; Boyer, Cyrille; Díaz, David Díaz (Polymer chemistry, 2021)
Carbon monoxide (CO) is being increasingly appreciated as a major physiological gasomediator and plays significant roles in different biological activities. However, site-specific delivery of this toxic gas faces major difficulties in the healthcare system in terms of unavailability of appropriate equipment for delivery. A well-known and most studied carbon monoxide releasing molecule (CORM) is tricarbonyldichlororuthenium( ii ) dimer (Ru 2 Cl 4 (CO) 6 ). However, its use as a therapeutic agent is restricted due to its poor water solubility and a short half-life. In order to solve this issues we have designed and synthesized a water-soluble methionine (methionine methacryloyloxyethyl ester (METMA)) and poly(ethylene glycol methyl ether methacrylate) containing block-copolymer via reversible addition-fragmentation chain transfer (RAFT) polymerization and attached the CORM in the methionine side chain units. Inductively coupled plasma optical emission spectrometry (ICP-OES) and FT-IR confirms the presence of CORM molecule into the polymer. The time-dependent CO release from CORM conjugated block-copolymer was investigated by a myoglobin assay. This CORM conjugated block-copolymer slowly and spontaneously released CO with sustained-release kinetics. Moreover, this CO-releasing polymer was able to prevent biofilm formation against Pseudomonas aeruginosa . A new water-soluble methionine-based CO releasing polymer shows slow and spontaneous release of CO with sustained-release kinetics, preventing biofilm formation against Pseudomonas aeruginosa .